In vivo challenges of anti-diabetic peptide therapeutics: Gastrointestinal stability, toxicity and allergenicity. (November 2020) - Yap, Pei Gee; Gan, Chee Yuen
Abstract: Background: A plethora of research has explored the potential of bioactive peptide as a new class of drug therapeutics, yet only a minute amount has successfully translated into clinical trials. Possible reasons may include several in vivo challenges such as the poor peptide bioavailability upon oral ingestion, peptide toxicity and peptide allergenicity. Bioinformatics offers a preliminary in silico prediction, screening and analysis of these properties. Scope and approach: In this review, anti-diabetic peptides were targeted and a total of 60 α-amylase, 60 α-glucosidase and 60 dipeptidyl peptidase-4 (DPP-4 ) inhibitory peptides were selected from the BioPEP-UWM database and recent literature. The peptide susceptibility to gastrointestinal enzyme degradation, toxicity and allergenicity were assessed in silico using the "enzyme action" tool from BioPEP-UWM, ToxinPred and AlgPred respectively. Key findings and conclusions: Most peptides were found susceptible to gastrointestinal degradation and could induce allergy to consumers. The cleaved peptides may subsequently exert other bioactivities. The gastrointestinal, toxicological and allergic challenges encountered or triggered by peptides as a result of complex interactions with the host environment were also highlighted. Therefore, researchers are strongly suggested to include these essential factors when assessing the anti-diabetic potential of peptides as clinical therapeutics with at least the aid of bioinformatics tools. Highlights: In vivo challenges faced by the reported anti-diabetic peptides were highlighted. Complex interactions between peptide and host GI environment were discussed. The peptide GI stability, toxicity and allergenicity were evaluated. Most peptides were found instable in the GI tract. Some peptides could induce allergy to consumers.